A century of changing fire management alters ungulate forage in a wildfire-dominated landscape. (12th April 2019) - Proffitt, Kelly M; DeVoe, Jesse; Barker, Kristin; Durham, Rebecca; Hayes, Teagan; Hebblewhite, Mark; Jourdonnais, Craig; Ramsey, Philip; Shamhart, Julee
Abstract: Forestry practices such as prescribed fire and wildfire management can modify the nutritional resources of ungulates across broad landscapes. To evaluate the influences of fire and forest management on ungulate nutrition, we measured and compared forage quality and abundance among a range of land cover types and fire histories within 3 elk ranges in Montana. We used historical fire data to assess fire-related variations in elk forage from 1900 to 2015. Fire affected summer forage more strongly than winter forage. Between 1900–1990 and 1990–2015, elk summer range burned by wildfire increased 242–1772 per cent, whereas the area on winter range burned by wildfire was low across all decades. Summer forage quality peaked in recently burned forests and decreased as time since burn increased. Summer forage abundance peaked in dry forests burned 6–15 years prior and mesic forests burned within 5 years. Forests recently burned by wildfire had higher summer forage quality and herbaceous abundance than those recently burned by prescribed fire. These results suggest that the nutritional carrying capacity for elk varies temporally with fire history and management practices. Our methods for characterizing nutritional resources provide a relatively straightforward approach for evaluating nutritional adequacy and tracking changes in forage associated with disturbances such as fire.